Islam and Woman in the Contemporary Arab World: An Interpretation of Rajaa al-Sanea’s Girls of Riyadh from Islamic Feminist Perspective - Khan, Tariq; Aziz Ahmad; Zulfiqar Ali (Journal of Islamic and Religious Studies, 2019)
The present position paper explores to examine Rajaa al-Sanea’s“Girls of Riyadh” (2005) from the Islamic feminist perspective. Also, the study highlights the model of western feminism epitomised in the narrative under reference, vis-à-vis the Islamic concept of feminism. Islamic feminism grants equal rights to women and ensures its implementation in the Islamic state and society, whereas Western-sponsored feminism dwells on the archetype of women’s liberalism. That, in turn, leads to an anarchic and chaotic society, because of its believing in bringing women not only equal to men but superseding them in socio-cultural positioning. In the existing situation, the novel decries phallocentric society of Saudi Arabia and aiming at replacing it by the sensate-secular feminism that believes in the undue autonomy of the women. In order to investigate the presence of overwhelming patrilineal mores, the study pursues Islamic feminism as a theoretical model and employs reader’s response technique as a methodology. More far the findings of the research are concerned, the researchers conclude that replacing the patriarchal autonomy in the said society by Islamic feminism is befitting and benefitting than to replace it by the western feminism.